Gender and methodology in the ancient Near East: approaches from assyriology and beyond - Adelina Millet Albà (Col·lecció Barcino Monographica Orientalia, 2018)
This collection of 23 essays, presented in three sections, aims to discuss women's studies as well as methodological and theoretical approaches to gender within the broad framework of ancient Near Eastern studies. The first section, comprising most of the contributions, is devoted to Assyriology and ancient Near Eastern archaeology. The second and third sections are devoted to Egyptology and to ancient Israel and biblical studies respectively, neighbouring fields of research included in the volume to enrich the debate and facilitate academic exchange. Altogether these essays offer a variety of sources and perspectives, from the textual to the archaeological, from bodies and sexuality to onomastics, to name just a few, making this a useful resource for all those interested in the study of women and gender in the past.